PENGETAHUAN DAN SIKAP TERHADAP KEGEMUKAN PADA ANAK DI ANTARA IBU-IBU MURID SD USIA 9-10 TAHUN DI KOTA BANDUNG - Mudjianto, Trintrin T.; Hermina, Hermina (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
KNOWLEDGE AND ATIITUDES TOWARD CHILDHOOD OBESITY AMONG MOTHERS OF 9-10 YEARS OLD ELEMENTARY SCHOOL CHILDREN IN BANDUNG CITY Background: Obesity is a major contributor for many degenerative diseases. In some populations, metabolic consequences of weight gain were onset as moderate overweight. There is a consistent trend of overweight and obesity in Indonesia and this was tendend to increase in younger adults and children. Objectives: This research aimed to explore and analyze the knowledge and attitudes in revand to childhood obesity among mothers of the Elementary School children (ESC). Methods: One hundred and twelve mothers who owned children aged 9-10 years who studied at the favorites ESC in Bandung City, West Java Province, involved in a cross-sectional study. The ESC was purposively selected, based on observation and data from the provincial government's education office showed that have many overweight students. Results: Mothers of the ESC who haved complete knowledge about obesity (3.6%). The mothers were lack of knowledge about obesity problem (63.4%). Most of the mothers felt unhappy or not proud if they have obese children (94.6%). Many mothers of the ESC felt not proud if their children were obese shown that they had a positive attitude if they got an appropriate information. Conclusions: Socialization of family nutrition awareness should be needed,with this way,every family, especially parents, is more care on childhood nutrition among others how to assess the children's nutritionalstatus and how to monitor their growth status. Childhood obesity could be prevented as early as possible if the nutrition awareness among parents is achieved. Keywords: childhood obesity, knowledge and attitudes, mother, Elementary School children